Analiza porównawcza strategii inwestowania na GPW w Warszawie - Piasecki, Krzysztof; Serafin, Marek; Świątczak, Łukasz (Comparative Analysis of Strategies of Investment on Warsaw Stock Exchange, 2006)
The essence of mathematics applications is critical discussion of applied formal model. This discussion is taken under context of real image of application domain. Thus schooling of critical approach plays a fundamental part of mathematics didactic. Mentioned education may be based on workshop discussion with students. There are described students investigations for weak points of predominant market strategy. Formal implementations are restricted to mathematical tools contained in program minimum for "Management and Marketing" studies. Full procedure of considerations and final result are presented. Unfortunately, inexhaustible variety "wonderful" market strategy gives occasion to multiple taking a advantage by described didactic case.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1117, s. 144-154